The Deeper Layers of Learning - Ruud van der Veen (Adult Education Research Conference, 2000)
The literature on adult education stresses often a shift from traditional reproductive learning towards communicative learning. This paper explores a further shift in late modernity towards ideosyncratic, aesthetic learning. Is there such a shift? If so, why? And what is it exactly? How would facilitation looks like?